The failure of corporate law: fundamental flaws & progressive possibilities - Greenfield, Kent (University of Chicago Press, 2010)
"When used in conjunction with corporations, the term “public” is misleading. Anyone can purchase shares of stock, but public corporations themselves are uninhibited by a sense of societal obligation or strict public oversight. In fact, managers of most large firms are prohibited by law from taking into account the interests of the public in decision making, if doing so hurts shareholders. But this has not always been the case, as until the beginning of the twentieth century, public corporations were deemed to have important civic responsibilities.